Protecting Location Information of Mobile Nodes in Mobile IPv6 - DENG, Robert H. (Institutional Knowledge at Singapore Management University, 2006)
Mobile IPv6 is an IP layer mobility protocol which allows mobile nodes to remain reachable while moving around in the Internet. In the current IETF Mobile IPv6 specifications (D. Johnson et al., 2004), when a mobile node roams, its location movement can be tracked by simply monitoring the IP addresses in IP packets. Recently, the issue of protecting location information in mobile IPv6 has received increasing attention, especially within the IETF and the 3GPP standard bodies. In this paper we propose a technique for hiding a mobile node's location movement information from eavesdroppers during route optimization and as well as from its correspondent node during reverse tunneling. The proposed technique is highly efficient and fully compatible with the base mobile IPv6 operation.